Waterborne polymer composites containing hybrid graphene/carbon nanotube filler: Effect of graphene type on properties and performance - Marija Prosheva, Maryam Ehsani, Yvonne Joseph, Radmila Tomovska, Jadranka Blazhevska Gilev (wileyonlinelibrary.com/journal/pc © 2023 Society of Plastics Engineers., 2023)
Polymer composites based on graphene/carbon nanotubes (G/CNT) and reduced graphene oxide/carbon nanotubes (rGO/CNT) were synthetized by in-situ miniemulsion polymerization containing 1 wt% hybrid filler with different ratio of G and CNT (10:1, 1.1, 1:10). From the hybrid aqueous dispersions obtained in that way polymer films were spontaneously formed at ambient conditions by water evaporation. The effect of the type of the graphene filler, G or rGO, on the properties and performance of polymer composites was studied. It was shown that G/CNT based composites presented improved morphology of the film due to better distribution of the filler and more organized structure of the film than that of rGO/CNT composites. The surface of the film was much smoother indicating more deepen filler within the polymer. Consequently, the G/CNT/polymer composites presented one order of magnitude increased Young's moduli and 60% lower water uptake than the neat polymer. Even though rGO/CNT/polymer composites presented also improved mechanical resistance, their water resistance was compromised probably due to the presence of hydrophilic functional groups that facilitated the water diffusion within the film.
Keywords: miniemulsion, G/CNT hybrids, rGO/CNT hybrids, waterborne composites